Synthesis and characterisation of CaO derived from cockleshell as a support for mixed-MgO and Fe₂O₃ catalysts for fame production using waste cooking oil - Salim, Ezzah Mahmudah (2018)
As an alternative for fossil diesel fuels, biodiesel has gained interest of most researchers recently in promoting environmentally sustainable fuels. With the presence of metal oxide modified cockleshell catalysts, biodiesel can be easily produced via transesterification of triglyceride with alcohol under reaction conditions. In this study, the magnesium oxide (MgO) and iron (III) oxide (Fe2O3) doped on natural CaO catalyst, which derived from cockleshell. MgO/CaO and Fe2O3/CaO were prepared and utilized by a single-step reaction process. The CaO were crushed and milled to obtain fine powder and calcined at 900 ⁰C for 6 h. Then, MgO/CaO and Fe2O3/CaO catalysts were synthesized using wet impregnation method; followed by calcination at 500 ⁰C for 4 h to produce heterogeneous catalyst with high activity and better selectivity which relatively giving a better performance in transesterification reaction. The catalysts were characterized in detail by both qualitative and quantitative methods such as X-ray fluorescence (XRF), X-ray diffraction (XRD), scanning electron microscope (SEM), scanning electron microscope-energy dispersive X-ray (SEM-EDX), thermal gravimetric analysis (TGA), temperature programmed desorption of ammonia and carbon dioxide (TPD-NH3 and TPD-CO2), and Brunauer-Emmett-Teller (BET) analyses, while the synthesized biodiesel was characterized using gas chromatography-flame ionization detector (GC-FID). The operating parameters such as methanol-to-oil molar ratio, catalyst amount and reaction time were investigated in order to optimize for the reaction condition for the biodiesel production. As a result, the optimum reaction parameters for MgO/CaO were 10:1 methanol-to-oil molar ratio, 4 h of reaction time, 2 wt. % of the catalyst loading and reaction temperature of 65 ⁰C shows 74 % FAME yield, meanwhile the optimum reaction parameters for Fe2O3/CaO were found to be 15:1 methanol-to-oil molar ratio, 3 h of reaction time and 1 wt. % of catalyst loading with reaction temperature of 65 ⁰C which produced 92 % FAME yield. The results revealed suggestively high potential of the heterogeneous MgO/CaO catalyst can be reusable at least 3 reaction cycles only while Fe2O3/CaO catalyst for direct conversion of waste cooking oil to biodiesel with the possibility to be reusable at least 5 reaction cycles without any reactivation process. Several physicochemical properties of waste cookingbased biodiesel produced was tested and agreed to ASTM D4052, ASTM D445, ASTM D464, ASTM D974 and EN 14214 standard.